Inovação social no campo da mobilidade urbana: um estudo com as bicicletas compartilhadas - Santos, Ana Sara Leite (2018)
In the current moment of technological dynamism in several sectors, with the advancement of technologies, development and application of innovations, in the field of urban mobility, new mobility services, transportation networks and shared vehicles have enabled opportunities and risks related to the promotion of quality of life, which are established according to the purpose of people. The bicycle sharing seen as a social innovation allows to be an environment of analysis due to its evolution and diffusion to promote changes in social practices (JAEGER-ERBEN; RÜCKERT-JOHN; SCHAFER, 2015). The social innovation related to a context emerges with the ideal of exploring the conjuncture of need and search for the improvement of the quality of life and attendance of the basic priorities of the individuals. This type of innovation can be as new alternatives that meet collective needs, generating new relationships capable of influencing society to act on the challenges they face (BUREAU OF EUROPEAN POLICY ADVISERS – BEPA, 2011), offering solutions to economic, social and environmental problems through activities or innovative services, with a focus on social change (ANDRÉ; ABREU, 2006; LÉVESQUE; LAJEUNESSE-CREVIER, 2005; MULGAN, 2006). It is the process of developing and implementation of effective solutions and often systemic aimed at social progress, being that social innovation is not prerogative in any organizational way but requires the active collaboration of government, business, and non-profit organizations (STANFORD GRADUATE SCHOOL OF BUSINESS, 2017). As a structure that can support and contribute to the advancement of understanding of social innovation, the use of analysis dimensions – proposed by researchers to evaluate contexts of a locality – gather central elements that allow the verification and analysis of this innovation in different parts of the process. Thus, the objective of this research is to analyze the elements that characterize bicycle sharing as a process of social innovation in the context of urban mobility, considering the dimensions of social innovation of Cloutier (2003), Tardif and Harrisson (2005), and André and Abreu (2006). This is an exploratory and descriptive study of a qualitative nature. The research strategy adopted is the study of multiple cases, and the research subjects involve the management (public power and operating company), the sponsoring companies and users of the bicycle sharing of the Bicicletar and Bicicleta Integrada projects, located in the city of Fortaleza, Ceará. The data were collected through participant observation, direct observation, semi-structured interview, and documentary and analyzed through content analysis using the NVivo 10 software. It is observed that the bicycle sharing as evolution of the concept of the bicycle bringing the remodeling of its objective: besides being useful as a means of transport, to contribute to the health of the individual and to reduce the pollution in the atmosphere – already existing characteristics – the vision of being a common good that allows the promotion of changes in existing social relations. Finding it from the perspective of social innovation makes it possible to visualize how ‘bike share’ systems alter the urban and social context, specifically in the locality under analysis. In addition to the fact that this study grants the rescue of concepts about social innovation and provides a new analytical environment, allowing to broaden the debate about the subject and bring theoretical-empirical contributions to the field of research.